Reversible alternation between bipolar and unipolar resistive switching in La-SrTiO3 thin films - 许定林 熊颖 唐明华 曾柏文 肖永光 王子平 (中国物理B：英文版, 2013)
The alternation from bipolar to unipolar resistive switching is observed in perovskite La0.01Sr0.99TiO3 thin films. These two switching modes can be activated separately depending on the compliance current （Icomp） during the electroforming process： with a higher Icomp （5 mA） the unipolar resistance switching behavior is measured, while the bipolar resistance switching behavior is observed with a lower Icomp （1 mA）. On the basis of I–V characteristics, the switching mechanisms for the URS and BRS modes are considered as being a change in the Schottky-like barrier height and/or width at the Pt/La-SrTiO3 interface and the formation and disruption of conduction filaments, respectively.